Robust and Secured Digital Audio Watermarking using Improved DWT-SVD-DFT Approach - N. Patel, Krunalkumar; A. Shah, Saurabh; B. Shah, Dipti (International Journal of Engineering and Technology, 2018)
Today, the use of digital data like image, audio and video is tremendously increasing due to the advancement in technology and internet revolution. With this advancement to attain the one’s ownership and copyrights for this digital data is the biggest challenge. Digital watermarking is one of the technique to attain one’s ownership and copyrights with securely. It is the technique in which the owner’s copyright information can be embedded into the original media either in the form of an image, audio, text or video. There are two main factors we need to observe for this digital audio watermarking to maintain the robustness as well as imperceptibility against the piracy, malicious attacks, and various transformation operations. Though there are many challenges to achieve this results, in this paper, our proposed audio watermarking technique is used to improve the robustness, imperceptibility of the embedded information with security. For Security, in our proposed work we are using synchronized secret key concept with DSSS encryption algorithm and two important powerful transformation methods used that are DWT (Discreet Wavelet Transformation) up to 4-level to get lowest frequency sub-band and after that DFT is applied to get lowest frequency from sub-band found by DWT in which the modifications are done and then SVD (Singular value Decomposition)is applied to it, so that original audio file does not have any impact of watermark bits to get the better robustness and imperceptibility.